4-Chlorothymol Exerts Antiplasmodial Activity Impeding Redox Defense System in Plasmodium falciparum - Kumar, Saurabh; Mina, Pooja Rani; Kumar, Ravi; Pal, Anirban; Ahmad, Ateeque; Tandon, Sudeep; Darokar, Mahendra P. (Frontiers in Pharmacology, 2021)
Malaria remains one of the major health concerns due to resistance in Plasmodium species towards existing drugs warranting an urgent need of new antimalarials. Thymol derivatives were known to exhibit enhanced antimicrobial activities, but not against Plasmodium. In present study, anti-plasmodial activity of thymol derivatives against chloroquine sensitive (NF-54) and resistant (K1) strains of Plasmodium falciparum was evaluated. Among the thymol derivatives tested, 4-Chlorothymol showed potent activity against sensitive and resistant (K1) strains of P. falciparum. 4-Chlorothymol was found to increase the ROS and RNS level. Further, 4-Chlorothymol could perturbed redox balance by modulating the enzyme activity of GST and GR. 4-Chlorothymol also showed synergy with chloroquine against chloroquine resistant P. falciparum. 4-Chlorothymol was found to significantly suppress the parasitemia and increase the mean survival time in in vivo assays. Interestingly, in in vivo assay, 4-Chlorothymol in combination with chloroquine showed higher chemo-suppression as well as enhanced mean survival time at a much lower concentrations as compare to individual doses of chloroquine and 4-Chlorothymol. These observations clearly indicate towards the potential use of 4-Chlorothymol as anti-malarial agent, which may also be effective in combination with exiting anti-plasmodial drugs against chloroquine resistant P. falciparum infection. In vitro cytotoxicity/haemolytic assay evidently suggest that 4-Chlorothymol is safe for further exploration for its therapeutic properties